Optimization simulated injection molding process for ultrahigh molecular weight polyethylene nanocomposite hip liner using response surface methodology and simulation of mechanical behavior. (May 2018) - Heidari, Behzad Shiroud; Davachi, Seyed Mohammad; Moghaddam, Amin Hedayati; Seyfi, Javad; Hejazi, Iman; Sahraeian, Razi; Rashedi, Hamid
Abstract: In this study, injection molding process of ultrahigh molecular weight polyethylene (UHMWPE) reinforced with nano-hydroxyapatite (nHA) was simulated and optimized through minimizing the shrinkage and warpage of the hip liners as an essential part of a hip prosthesis. Fractional factorial design (FFD) was applied to the design of the experiment, modeling, and optimizing the shrinkage and warpage of UHMWPE/nHA composite liners. The Analysis of variance (ANOVA) was applied to find the importance of operative parameters and their effects. In this experiment, seven input parameters were surveyed, including mold temperature (A), melt temperature (B), injection time (C), packing time (D), packing pressure (E), coolant temperature (F), and type of liner (G). Two models were capable of predicting warpage and volumetric shrinkage (%) in different conditions with R 2 of 0.9949 and 0.9989, respectively. According to the models, the optimized values of warpage and volumetric shrinkage are 0.287222 mm and 13.6613%, respectively. Meanwhile, a finite element analysis (FE analysis) was also carried out to examine the stress distribution in liners under the force values of demanding and daily activities. The Von-Mises stress distribution showed that both of the liners can be applied to all activities with no failure. However, UHMWPE/nHA liner is more resistant to the highest loads than UHMWPE liner due to the effect of nHA in the nanocomposite. Finally, according to the results of injection molding simulations, optimization, structural analysis as well as the tensile strength and wear resistance, UHMWPE/nHA liner is recommended for the production of a hip prosthesis. Graphical abstract: fx1 Highlights: Injection molding simulation and optimization of UHMWPE nanocomposite hip liners. FFD was used to modeling and optimizing the shrinkage and warpage of the liners. Interaction effect of process factors studied using the response surfaces plots. FE analysis showed that UHMWPE and UHMWPE/nHA hip liner could be used for all daily activities. UHMWPE/nHA is the best candidate for hip liner production due to lower shrinkage, warpage, wear volume and also higher yield strength.